Cost Effectiveness of DCISionRT for Guiding Treatment of Ductal Carcinoma in Situ. Issue 2 (31st January 2020) - Raldow, Ann C; Sher, David; Chen, Aileen B; Punglia, Rinaa S
Abstract: The DCISionRT test estimates the risk of an ipsilateral breast event (IBE) in patients with ductal carcinoma in situ (DCIS) as well as the benefit of adjuvant radiation therapy (RT). We determined the cost-effectiveness of DCISionRT using a Markov model simulating 10-year outcomes for 60-year-old women with DCIS based on nonrandomized data. Three strategies were compared: no testing, no RT (strategy 1); test all, RT for elevated risk only (strategy 2); and no testing, RT for all (strategy 3). We used utilities and costs from the literature and Medicare claims to determine incremental cost-effectiveness ratios and examined the number of women irradiated per IBE prevented. In the base-case scenario, strategy 1 was the cost-effective strategy. Strategy 2 was cost-effective compared with strategy 3 when the cost of DCISionRT was less than $4588. The number irradiated per IBE prevented were 8.37 and 15.46 for strategies 2 and 3, respectively, relative to strategy 1.